Factors Affecting Quality of Accounting Information and Its Impact on Local Government Fixed Assets Management's Effectiveness: A Study on Local Government of Indonesia - Dharma, Fitra; Metalia, Mega; Sembiring, Sari Indah Oktanti (The Indonesian Journal of Accounting Research, 2023)
Inseparable from managing regional fixed assets is the quality of information or data utilized by each unit. The quality of accounting information in government is heavily dependent on the leadership's commitment, the effectiveness of internal control, and the execution of good governance, according to various published works; nevertheless, this must be demonstrated further. Consequently, this study aims to investigate the link and size of the influence of these three elements on the quality of accounting information and their impact on the efficacy of local government fixed asset management. In Indonesia, 34 provincial governments, 416 district governments, and 98 city governments were surveyed for this quantitative research. This study included 529 participants. The research data was gathered using a questionnaire instrument that included in-person interviews—data analysis using the Structural Equation Modeling (SEM) method with Lisrel 8.8 statistical software. The explanation of research findings is both descriptive and causally explanatory. In general, local governments in Indonesia have excellent accounting data and management of fixed assets. In carrying out local government tasks, the local government has also built an effective internal control system and excellent governance. The study's findings demonstrate that the effectiveness of internal control and the function of good governance substantially impact the quality of accounting data. Similarly, leadership commitment, the importance of good governance, and the accuracy of accounting information substantially impact the success of fixed asset management. However, internal control efficacy does not significantly impact managing local governments' fixed assets.